2021
DOI: 10.47203/ijch.2021.v33i04.012
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic and Clinical Profile of Drug Resistant Tuberculosis Patients in a Tertiary Care Centre of Kolkata

Abstract: Background: Drug resistant tuberculosis is a major public health threat that hinders progress in tuberculosis control worldwide. In 2019, India contributed highest cases of TB (27%) Worldwide. In 2019, 3.3% of new TB cases and 18% of previously treated cases had MDR/RRTB worldwide and India (27%) had the largest share of the global burden. This study was done to find out the sociodemographic and clinical profile of drug resistant TB patients. Methodology: It is an observational descriptive study with cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The most common form of substance use was smoking 2 (27%), followed by alcohol 27 (26%), with duration of more than 5 years was most common among study participants. Similar findings were observed by Mukherjee et al (2015) and Basu et al (2021) found that history of smoking (28%), and alcohol intake (28%) were present. Out of 527 cases tracking in this study, 103 (19.5%) developed the symptoms suggestive of TB.…”
Section: Table3 Retrospective Analysis Of Relapses Depending On Initi...supporting
confidence: 86%
See 1 more Smart Citation
“…The most common form of substance use was smoking 2 (27%), followed by alcohol 27 (26%), with duration of more than 5 years was most common among study participants. Similar findings were observed by Mukherjee et al (2015) and Basu et al (2021) found that history of smoking (28%), and alcohol intake (28%) were present. Out of 527 cases tracking in this study, 103 (19.5%) developed the symptoms suggestive of TB.…”
Section: Table3 Retrospective Analysis Of Relapses Depending On Initi...supporting
confidence: 86%
“…it is not known whether the patient's body was completely eliminated (eradication) from Tuberculosis. In previous studies (Mathur et al, 2019;Sharma et al, 2019;Basu et al, 2021), pointed to factors contributing to the reactivation of the tuberculosis process, which may be facilitated by labour migration with the likelihood of superinfection with another strain of mycobacterium TB. Despite the repeated visits, this study could not track more than onefourth (213) of cases mainly due to the incomplete or wrong address, migration or death due to some unknown diagnosis.…”
Section: Table3 Retrospective Analysis Of Relapses Depending On Initi...mentioning
confidence: 99%
“…MDR: Multidrug resistant, XDR: Extensively drug resistant not accessible 20. Moreover, another study by Mulisa et al, reported an extremely high unfavorable treatment outcome rate (81%), due to driven factors such as behavioral factors like alcoholism, chat chewing, then concurrent chronic disease, previous history of tuberculosis, and irrational antacid use for gastritis while being treated for tuberculosis.…”
mentioning
confidence: 99%